Structured approach with primary and secondary survey for major trauma care: an overview of reviews - Silvia Gianola; Silvia Bargeri; Annalisa Biffi; Stefania Cimbanassi; Daniela D’Angelo; Daniela Coclite; Gabriella Facchinetti; Alice Josephine Fauci; Carla Ferrara; Marco Di Nitto; Antonello Napoletano; Ornella Punzo; et al. (World Journal of Emergency Surgery, 2023)
Abstract Background A structured approach involves systematic management of trauma patients. We aim to conduct an overview of reviews about the clinical efficacy and safety of structured approach (i.e., primary and secondary survey) by guideline checklist compared to non-structured approach (i.e. clinical examination); moreover, routine screening whole-body computer tomography (WBCT) was compared to non-routine WBCT in patients with suspected major trauma. Methods We systematically searched MEDLINE (PubMed), EMBASE and Cochrane Database of Systematic Reviews up to 3 May 2022. Systematic reviews (SRs) that investigated the use of a structured approach compared to a non-structured approach were eligible. Two authors independently extracted data, managed the overlapping of primary studies belonging to the included SRs and calculated the corrected covered area (CCA). The certainty of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. Results We included nine SRs investigating two comparisons in stable trauma patients: structured approach vs non-structured approach (n = 1) and routine WBCT vs non-routine WBCT (n = 8). The overlap of included primary studies was generally high across outcomes (CCA ranged between 20.85 and 42.86%) with some discrepancies in the directions of effects across reviews. The application of a structured approach by checklist may improve adherence to guidelines (e.g. Advanced Trauma Life Support) during resuscitation and might lead to a reduction in mortality among severely injured patients as compared to clinical examination (Adjusted OR 0.51; 95% CI 0.30–0.89; p = 0.018; low certainty of evidence). The use of routine WBCT seems to offer little to no effects in reducing mortality and time spent in emergency room or department, whereas non-routine WBCT seems to offer little to no effects in reducing radiation dose, intensive care unit length of stay (LOS) and hospital LOS (low-to-moderate certainty of evidence). Conclusions The application of structured approach by checklist during trauma resuscitation may improve patient- and process-related outcomes. Including non-routine WBCT seems to offer the best trade-offs between benefits and harm. Clinicians should consider these findings in the light of their clinical context, the volume of patients in their facilities, the need for time management, and costs.